The Islam and Insurance In Indonesia - Mu'adil Faizin (Nizham Jurnal Studi Keislaman, 2017)
The development of Islamic business thinking encourages a variety of sharia-based business practices, Sharia Insurance, meeting the two variables "Islam And Insurance", is one of them. Insurance is assumed as an industry with the principle of mutual help, but some assess the Takaful Insurance in Indonsia is not clear because it has business activities in it. Therefore, researchers raised the issue of Islam and Insurance In Indonesia. This study of literature review using content analysis method. Research results that Sharia Insurance has a historical basis called the concept of at-ta'min at-ta'awuniy, as well as ethical basis of ta'awun and takaful. There are 2 (two) Takaful products in Indonesia; first, products with elements of savings (saving); second, the product without the element of savings (non-saving).